Environmental drivers of antimicrobial resistance – cadmium contamination & antibiotic resistance in soil samples from a rural airstrip. - Heydari A; Kim N; Biggs P; Horswell J; Gielen G; Siggins A; Bromhead C; Palmer B (Massey University, 2023)
Environmental contamination with both inorganic and organic compounds is a growing problem globally. In this study we investigated links between heavy metal contamination of soil and selection for antibiotic resistance in soil bacteria. Soil samples taken at 10 m intervals along the length of a 70 m transect of a rural airstrip used for aerial topdressing located in Belmont Regional Park near Wellington were analysed for heavy metal content and resistance profiles of heterotrophic bacteria cultured were characterised. A gradient of cadmium contamination (a known contaminant of superphosphate fertiliser) ranging from 1.14 to 7.20 mg kg-1 of dry soil was detected in the samples. Total bacterial counts were significantly reduced at the most heavily contaminated subsites, with >60% of isolates resistant to 0.01 mM CdCl2. The ratio of antibiotic resistant isolates to total CFU was significantly higher at the most contaminated compared to the least contaminated subsite for five common antibiotics. Metagenomic analysis of total DNA from three subsites showed significantly different profiles at all taxonomic levels. This suggests environmental contamination with heavy metals may be a significant and under-appreciated driver of selection for antimicrobial resistance.
Keywords: antimicrobial resistance; heavy metals; metagenomics; soil microbiology